Review of methods for measurement of signal to noise ratio of image intensifier tubes - Chrzanowski, Krzysztof (Metrology and Measurement Systems, 2026)
Image intensifier tube is the most important block of night vision devices that enable vision at low illumination conditions and are of critical importance for military and security agencies. SNR (signal to noise ratio) is one of two most important parameters of image intensifier tubes. This paper presents a review of methods used to measure the SNR of image intensifier tubes. Reasons why SNR test results of the same tube carried out by different laboratories often differ significantly are presented.